Fossil and Modern Clam Shrimp (Branchiopoda: Spinicaudata, Laevicaudata): The World’s First Clam Shrimp Symposium and a Celebration of Brian V. Timms - Rogers, D. Christopher (Zool Stud, 2020)
This special volume of Zoological Studies is the result of a symposium entitled “Fossil and Modern Clam Shrimp” held at the midyear meeting of The Crustacean Society in May of 2019. This symposium is the first ever focusing on clam shrimp, and the first conference where both palaeontologists and biologists specialising in these animals were able to come together. The papers presented here provide insight into the palaeontology, biology, ecology, taxonomy and phylogeny of the clam shrimp. This chapter introduces the symposium, its aims, and the resulting research, presented in the subsequent chapters. In addition, in this symposium we celebrate our great friend Brian V. Timms, who has mentored so many of us, brought us on various excursions across Australia, and has done more to advance Australian branchiopod studies than anyone else in history.